A Pilot Study of Mercury Distribution in the Carapace of Four Species of Sea Turtles from Northeastern Brazil. - Barrios-Rodríguez, César Augusto (2023)
Scutes present very complex morphologies with different growth rates at different areas of the carapace that can change the accumulation process of essential and non-essential metals. To infer the effects of morphology and growth on Hg concentrations in scutes, we mapped them in the carapace of one individual of four species of sea turtles sampled along the Brazilian coast. The results showed that Hg concentrations were higher in the vertebral scutes of Chelonia mydas and Eretmochelys imbricata suggesting variation in growth rates of different carapace areas since the vertebral area is the first to develop prior to costal areas. Caretta caretta and Lepidochelys olivacea did not show differences between carapace areas. The preliminary data from this pilot study indicate that vertebral scutes may be suitable for monitoring Hg in C. mydas and E. imbricata, since they reflect longer exposure period. A species-to-species comparison of Hg concentrations is not possible due to the small number of sampled individuals, nevertheless, E. imbricata showed remarkably lower Hg concentrations compared to the other three species. Further studies are required for all four species, with a larger number of individuals, preferentially of varying life stages, due to the unknown effects of different diets, Hg exposure, and migration histories